A broadband electret-based vibrational energy harvester using soft magneto-sensitive elastomer with asymmetrical frequency response profile. (4th September 2019) - Yang, Zhaoshu; Tang, Lihua; Tao, Kai; Aw, Kean
Abstract: This letter reports a broadband electret-based vibrational energy harvester (eVEH) targeting at applications in low frequency (4–10 Hz) and low excitation (0.1–0.2 g) scenarios. A soft magneto-sensitive elastomer (SMSE) cantilever with low resonance and strong softening nonlinear behaviour is utilized as the broadband oscillator. A spring suspended end-stopper attached to the electret converts low frequency excitation of the SMSE cantilever to high frequency vibrations of the eVEH for efficiency enhancement. An asymmetrical frequency response profile for the SMSE cantilever is intentionally designed to preserve its softening behaviour for broadband performance when the end-stopper is engaged. A proof-of-concept prototype is fabricated and the experiment shows that within a working frequency range of 4.0–8.2 Hz, the eVEH can harvest the average power output of 40.23 μ W under a base excitation of 0.2 g.